Pendidikan Agama Islam Dalam Sistem Pendidikan Nasional - Khotimah, Annisa Husnul; Azizah, Afiq; Ginting, Nurhanisa; Siddik, Mhd Fajar; Darlis, Ahmad (At-Tadris: Journal of Islamic Education, 2023)
Islamic religious education is a learning carried out by a person or an educational institution which will later provide Islamic religious material in it. Islamic Religious training also does not escape importance of the national education system. It can be seen from the system of national education, which is based on Law No. 20 of 2003 which has provided breadth to Islamic religious education with all forms and models of learning in it. In Indonesia, Islamic religious education is a foundation and a strong basis to be able to instill Islamic valuesthrough the educational process. This is of course very related to Islamic religious education to national education. In connection with Islamic religious education which has the second position in the national education system, later it will be shown here that the position and position of the Islamic religious education system will affect the national education system, the reality of Islamic religious education and the various aspects that complement it.